Men and mental ill health. (2nd August 2019) - Barber, Christopher
Abstract : Although mental ill health is 'gender blind' in that it affects people of all genders, some forms of mental ill health appear to affect men and women in differing numbers and percentages, and sometimes with differing responses and outcomes. This article explores the statistics around men and mental ill health, how men respond to mental ill health and the roles of the nurse in supporting men who experience mental ill health.